Pattern of Multicultural Insights Development as a Strategy for Adaptation of Midwifery Students - K., Hairuddin (Journal of Education Research and Evaluation, 2021)
This study aims to investigate the pattern, to know the process and to determine the supporting and inhibiting factors for developing multicultural insights. This research used descriptive qualitative method through observation, interviews and documentation. The data validity test used triangulation, while data analysis technique used miles and Huberman interactive analysis, namely reduction, presentation and data verification or conclusion. The results of study showed that diverse cultures, multicultural insights can increase understanding of Indonesian multiculturalism, especially midwifery students. While the process of developing multicultural insights used formal and informal stages, as for the supporting and inhibiting factors of developing insight in midwifery students including the spirit of diversity is fundamental, interaction with students in class when taking ISBD courses is quite conducive to multicultural application, there is a balance between theories and practice and it has been integrated